Lara and the gray mare - Duey, Kathleen (New York : Puffin Books, 2005)
While her father is away fighting the Normans and other Irish clans, nine-year-old Lara works hard to help harvest food and also cares for the pregnant gray mare that she loves.
Ages 8 up.
Accelerated Reader AR
Keywords: Horses -- Juvenile fiction; Horses -- Fiction; Ireland -- History -- Juvenile fiction; Ireland -- History -- Fiction; Historical fiction